2013
DOI: 10.1007/s11064-013-1033-0
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy in Ischaemia/Reperfusion Induced Cerebral Injury

Abstract: Mitochondrial autophagy (Mitophagy), the specific autophagic elimination of mitochondria, has been related with several forms of degenerative disease and mitochondrial dysfunction. It is involved in multiple cellular processes. In addition to one of its established key roles in the maintenance of normal cellular phenotype and function, there is growing interest in the concept that targeted modulation of mitophagy may reduce cerebral ischaemia/reperfusion injury. Induction of mitophagy results in selective clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Nonetheless, an increase in LC3B-II on the first day post-ischemia has been reported in neuronal degeneration ( Adhami et al, 2006 ; Li and McCullough, 2010 ), and it has been suggested that the pharmacological inhibition of autophagy reduces cerebral infarct volume ( Kubota et al, 2010 ; Meloni et al, 2011 ; Gao et al, 2012 ). However, autophagic activity may play an important role in neuroprotection after an ischemic event, resulting in a beneficial effect on the cerebral cortex and hippocampus to prevent protein aggregation after stroke ( Rami, 2009 ; Guo et al, 2010 ; Liu et al, 2010 , 2013a , b ; Zhou et al, 2011 ), and autophagic degradation has been proposed as an important regulator of hyperphosphorylated tau levels after an acute injury (e.g., in CI; Liu et al, 2010 ; Marino et al, 2011 ; Schaeffer and Goedert, 2012 ), which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Nonetheless, an increase in LC3B-II on the first day post-ischemia has been reported in neuronal degeneration ( Adhami et al, 2006 ; Li and McCullough, 2010 ), and it has been suggested that the pharmacological inhibition of autophagy reduces cerebral infarct volume ( Kubota et al, 2010 ; Meloni et al, 2011 ; Gao et al, 2012 ). However, autophagic activity may play an important role in neuroprotection after an ischemic event, resulting in a beneficial effect on the cerebral cortex and hippocampus to prevent protein aggregation after stroke ( Rami, 2009 ; Guo et al, 2010 ; Liu et al, 2010 , 2013a , b ; Zhou et al, 2011 ), and autophagic degradation has been proposed as an important regulator of hyperphosphorylated tau levels after an acute injury (e.g., in CI; Liu et al, 2010 ; Marino et al, 2011 ; Schaeffer and Goedert, 2012 ), which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Autophagy is the only mechanism by which entire organelles are engulfed and recycled through the lysosomal pathway (Liu et al, 2013). Mitophagy refers to a specific autophagic phenomenon, in which cells are selectively cleared of damaged mitochondria through autophagy (Yang and Klionsky, 2010;Fimia et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, mitochondrial damage was alleviated indicating relative integrity of cristae structure, and a few structures of autophagy and mitophagy appeared in the XXMD- or CsA-treated group. Mitochondria are those essential organelles for generation and action of reactive oxygen species (ROS) in brain cells [ 36 ]. Damaged mitochondria following ischemia and reperfusion could result in the increase in ROS, and meanwhile, mitochondrial ATP levels are considered an indicator of cell death [ 14 ].…”
Section: Discussionmentioning
confidence: 99%